Association Between Age at Diagnosis of Atrial Fibrillation and Subsequent Risk of Ischemic Stroke - Cheng, Yun‐Jiu; Deng, Hai; Wei, Hui‐Qiang; Lin, Wei‐Dong; Liang, Zhuomin; Chen, Yili; Dong, Yugang; Fang, Xian‐Hong; Liao, Hong‐Tao; Wu, Shu‐Lin; Liu, Fang‐Zhou; Xue, Yu‐Mei; et al. (Journal of the American Heart Association, 2025)
Atrial fibrillation (AF) significantly increases the ischemic stroke risk. However, the relationship between age at diagnosis of AF and subsequent stroke risk remains poorly understood. We analyzed data from 5 prospective cohorts: ARIC (Atherosclerosis Risk in Communities) study, CHS (Cardiovascular Health Study), CARDIA (Coronary Artery Risk Development in Young Adults), MESA (Multi-Ethnic Study of Atherosclerosis), and Framingham Heart Study (including Offspring cohort and the Third-Generation cohorts). Cox regression models and competing risk survival analyses were used to assess incidence rates and hazard ratios (HRs) for ischemic stroke stratified by age groups. Among 47 239 participants (median follow-up: 21.1 years), 6689 (14.2%) developed AF, and 536 (8.0%) subsequently experienced ischemic stroke. Younger age at AF diagnosis was significantly associated with a higher ischemic stroke risk. Fully adjusted HRs for ischemic stroke were 5.35 (95% CI, 3.56-8.03), 2.99 (95% CI, 2.32-3.86), 2.13 (95% CI, 1.75-2.58), and 1.93 (95% CI, 1.59-2.34) for AF diagnosed at ages 55, 65, 75, and 85, respectively. Compared with participants without AF at age 55, HRs for ischemic stroke were 7.30 (95% CI, 3.27-16.31) for AF diagnosed >10 years earlier, 4.98 (95% CI, 2.99-8.29) for 6 to 10 years earlier, and 4.60 (95% CI, 1.48-14.34) for ≤5 years earlier ( -trend <0.001). The presence of AF yielded a 13.9 years earlier occurrence of ischemic stroke among those with AF diagnosis at 55 years compared with 1.5 years earlier at age 85. Younger age at AF diagnosis was associated with a higher risk of subsequent ischemic stroke.